Autogenous bone graft with or without a calcium sulfate barrier in the treatment of class II furcation defects: A histologic and histometric study in dogs - Deliberador, Tatiana M. [UNESP]; Nagata, Maria J.H. [UNESP]; Furlaneto, Flávia A.C. [UNESP]; Melo, Luiz G.N. [UNESP]; Okamoto, Tetuo [UNESP]; Sundefeld, Maria L.M.M. [UNESP]; Fucini, Stephen E. (Wiley, 2006)
Background: The purpose of this study was to histologically evaluate the healing of surgically created Class II furcation defects treated using an autogenous bone (AB) graft with or without a calcium sulfate (CS) barrier. Methods: The second, third, and fourth mandibular premolars (P2, P3, and P4) of six mongrel dogs were used in this study. Class II furcation defects (5 mm in height × 2 mm in depth) were surgically created and immediately treated. Teeth were randomly divided into three groups: group C (control), in which the defect was filled with blood clot; group AB, in which the defect was filled with AB graft; and group AB/CS, in which the defect was filled with AB graft and covered by a CS barrier. Elaps were repositioned to cover all defects. The animals were euthanized 90 days post-surgery. Mesio-distal serial sections were obtained and stained with either hematoxylin and eosin or Masson's trichrome. Histometric, using image-analysis software, and histologic analyses were performed. Linear and area measurements of periodontal healing were evaluated and calculated as a percentage of the original defect. Percentage data were transformed into arccosine for statistical analysis (analysis of variance; P<0.05). Results: Periodontal regeneration in the three groups was similar. Regeneration of bone and connective tissue in the furcation defects was incomplete in most of the specimens. Statistically significant differences were not found in any of the evaluated parameters among the groups. Conclusion: Periodontal healing was similar using surgical debridement alone, AB graft, or AB graft with a CS barrier in the treatment of Class II furcation defects.
Keywords: Animal research; Bone grafting; Calcium sulfate/therapeutic use; Guided tissue regeneration; Periodontal diseases/therapy; calcium sulfate; eosin; hematoxylin; ketorolac; analgesia; analysis of variance; animal euthanasia; animal experiment; animal model; animal tissue; autograft; blood clot; bone regeneration; bone transplantation; calculation; computer program; connective tissue; controlled study; debridement; disease classification; dog; healing; histology; histometry; image analysis; male; nonhuman; periodontal disease; postoperative care; premolar tooth; random sample; statistical significance; tissue flap; treatment outcome